2005
DOI: 10.1007/s00775-004-0622-4
|View full text |Cite
|
Sign up to set email alerts
|

The intrinsic axial ligand effect on propene oxidation by horseradish peroxidase versus cytochrome P450 enzymes

Abstract: The axial ligand effect on reactivity of heme enzymes is explored by means of density functional theoretical calculations of the oxidation reactions of propene by a model compound I species of horseradish peroxidase (HRP). The results are assessed vis-a-vis those of cytochrome P450 compound I. It is shown that the two enzymatic species perform C=C epoxidation and C-H hydroxylation in a multistate reactivity scenario with Fe(III) and Fe(IV) electromeric situations and two different spin states, doublet and quar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 45 publications
1
53
0
Order By: Relevance
“…We used propene as a substrate since this is the smallest model in which competitive alkyl hydroxylation and C=C bond epoxidation mechanisms can be studied. [8,9] Received: October 31, 2005 Published online: February 10, 2006 . Keywords: density functional calculations · enzyme catalysis · enzyme models · epoxidation · hydroxylation…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used propene as a substrate since this is the smallest model in which competitive alkyl hydroxylation and C=C bond epoxidation mechanisms can be studied. [8,9] Received: October 31, 2005 Published online: February 10, 2006 . Keywords: density functional calculations · enzyme catalysis · enzyme models · epoxidation · hydroxylation…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Earlier work on heme-type oxoiron porphyrin models for P450 and HRP systems showed that the regioselectivity of propene epoxidation versus methyl group hydroxylation is dependent on small environmental perturbations. [8,9] The electronic ground state of Cpd I of the heme enzymes P450 and HRP is a set of nearly degenerate quartet and doublet spin states, [10] which creates two-state reactivity patterns with competing reaction mechanisms on the two spin state surfaces. [11] In particular, the doublet spin state leads to product formation via a short-lived intermediate, whereas from the quartet spin state a long-lived intermediate is reached, which makes side-reactions leading to by-products possible.…”
mentioning
confidence: 99%
“…Interestingly, Shaik and co-workers further proposed that the preference for C− −C epoxidation shown by P450 CpdI in theoretical studies results from not accounting for the polarizing environment found in P450. Thus, a more refined model, including polarization effects, was developed, which accounted for the available experimental observations [95,96].…”
Section: Comparison With Experimental Datamentioning
confidence: 99%
“…The major structural difference between peroxidases and cytochrome P450s is that substrates can approach the heme iron only in the case of cytochrome P450. Therefore, the actual reaction between the oxidized Fe-TAML and a substrate may more closely mimic cytochrome P450 enzymes because in catalysis, peroxidase reactivity is limited by the access of the substrate to the oxidized iron [5,80,81]. At our present state of understanding, Fe-TAMLs are well described as being green oxidation catalysts.…”
Section: Resultsmentioning
confidence: 99%